2020
DOI: 10.3389/fbioe.2020.00703
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Manufacturing for Recombinant Snakebite Antivenoms

Abstract: Snakebite envenoming is a neglected tropical disease that affects millions of people across the globe. It has been suggested that recombinant antivenoms based on mixtures of human monoclonal antibodies, which target key toxins of medically important snake venom, could present a promising avenue toward the reduction of morbidity and mortality of envenomated patients. However, since snakebite envenoming is a disease of poverty, it is pivotal that next-generation therapies are affordable to those most in need; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Recently, recombinant antivenoms based on oligoclonal mixtures of human antibodies have been proposed as a cost-competitive alternative to current antivenoms (1922) . Such recombinant antivenoms may offer safer and more efficacious snakebite envenoming therapy due to their compatibility with the human immune system and the possibility of only including efficacious antibodies, targeting medically relevant snake toxins, in the antivenom mixture (18) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, recombinant antivenoms based on oligoclonal mixtures of human antibodies have been proposed as a cost-competitive alternative to current antivenoms (1922) . Such recombinant antivenoms may offer safer and more efficacious snakebite envenoming therapy due to their compatibility with the human immune system and the possibility of only including efficacious antibodies, targeting medically relevant snake toxins, in the antivenom mixture (18) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, recombinant antivenoms based on oligoclonal mixtures of human antibodies have been proposed as a cost-competitive alternative to current antivenoms (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other biologics, classical monoclonal antibodies produced with long-stablished hybridoma technology are acceptable as the gold standard in immunotherapy and diagnostics [ 78 , 79 , 80 ]. However, these classical monoclonal antibodies need more support costs and they are difficult for massive production compared to their counterpart nanobodies [ 81 , 82 , 83 ]. The high production cost of classical monoclonal antibodies, limited tissue penetration, and less favourable pharmacokinetic stability have stimulated the use of smaller alternative antibody formats, such as the antigen binding fragments, single-chain variable fragments, and nanobodies [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combined, these studies have demonstrated the feasibility of using phage display technology for the discovery of such molecules, as well as the potential utility of formulating these into so-called ‘recombinant antivenoms’ ( Laustsen, 2016a ). One of the challenges for these types of endeavors is, however, to develop sufficiently broadly-neutralizing monoclonal antibodies, which is a necessity for feasible recombinant antivenom manufacture, as the inclusion of antibodies that are able to cross-neutralize multiple toxins allow the manufacturer to limit the number of antibodies needed in a recombinant antivenom formulation ( Jenkins and Laustsen, 2020 ; Ledsgaard et al, 2018 ). Therefore, recent studies have focused on devising simple, rational methods that allow for facile discovery of antibodies with such properties.…”
Section: Therapeutic Application Of Monoclonal Antibodies and Antibody Fragmentsmentioning
confidence: 99%
“…In contrast to many other disease areas, such as oncology and autoimmune diseases, where antibodies have successfully entered the clinic, SBE is fundamentally different in nature: It is acute, a very large number of targets of great molecular complexity must be neutralized, therapy only needs to be administered over a short period of time, and the majority of patients come from impoverished regions of the tropics ( Laustsen, 2019 ). This puts certain constraints on what antibody formats are likely to be useful for treating this pathology, as well as feasible to develop and cost-competitive to manufacture ( Jenkins and Laustsen, 2020 ; Knudsen et al, 2019 ; Laustsen et al, 2017 ; Laustsen and Dorrestijn, 2018 ). Generally, different antibody formats have different advantages and disadvantages ( Table 2 ), but it is important that the antibody format of choice is compatible with the human immune system and therefore safe, that the format is versatile and allows for facile development of antibodies that can neutralize different toxin families, that the format is easy and low-cost to manufacture, and that the format can be engineered to bind toxins with very high affinity ( Knudsen et al, 2019 ; Laustsen et al, 2018a ).…”
Section: Advantages and Disadvantages Of Different Antibody Formatsmentioning
confidence: 99%